The History, Use, Disposition and Environmental Fate of Agent Orange - Young, Alvin Lee.; SpringerLink (Online service) (New York, NY : Springer New York, 2009)
For almost four decades, controversy has surrounded the tactical use of herbicides in Southeast Asia by the United States military. Few environmental or occupational health issues have received the sustained international attention that has been focused on Agent Orange, the major tactical herbicide deployed in Southern Vietnam. With the opening and establishment of normal relations between the United States and the Socialist Republic of Vietnam in 1995, the time has come for a thorough re-examination of the military use of Agent Orange and other "tactical herbicides" in Southern Vietnam, and the subsequent actions that have been taking place since their use in Vietnam. The United States Department of Defense has had the major role in all military operations involving the use of tactical herbicides, including that of Agent Orange. This included the Department's purchase, shipment and tactical use of herbicides in Vietnam, its role in the disposition of Agent Orange after Vietnam, its role in conducting long-term epidemiological investigations of the men of Operation RANCH HAND, and its sponsorship of ecological and environmental fate studies. This book was commissioned by The Office of the Deputy Under Secretary of Defense (Installations and Environment) with the intent of providing documentation of the knowledge on the history, use, disposition and environmental fate of Agent Orange and its associated dioxin.
Vietnam and the Agent Orange Controversy Revisited -- A History of the Development and Procurement of Tactical Herbicides -- The Military Use of Tactical Herbicides in Vietnam -- Removal from Vietnam and Final Disposition of Agent Orange -- Agent Orange and its Dioxin Contamination -- The Testing of Aerial Spray Equipment, and Ecological Impacts of the Programs at Eglin Air Force Base, Florida -- Monitoring Studies of Former Agent Orange Storage Sites in Mississippi and Johnston Island -- Agent Orange and Dioxin Remediation and the Return to Vietnam.
Keywords: ENVIRONMENTAL SCIENCES; ENVIRONMENTAL MANAGEMENT; ENVIRONMENTAL TOXICOLOGY; ENVIRONMENT; ECOTOXICOLOGY; ENVIRONMENTAL MANAGEMENT; PUBLIC HEALTH/GESUNDHEITSWESEN.